Bridging Faculty–Student Gaps in Experiential Management Education : An Indian Perspective - D., Shahanaz; D., Masthan (Prabandhan: Indian Journal of Management, 2025)
Purpose : This study investigated the gaps between faculty and students in experiential management education within the Indian context by exploring the interrelated challenges faced by both stakeholders. Methodology : A questionnaire comprising closed and open-ended questions was distributed to a random sample of 77 faculty members and 274 students from nine affiliated colleges. Responses were examined through content analysis and descriptive statistics to identify key challenges contributing to the disconnection. Findings : A significant gap in understanding others’ perspectives existed. Students were facing several social and psychological challenges, unknown to faculty members, who perceived them as disinterested and hesitant to engage. Conversely, students criticized the inadequate support from faculty and management, while faculty highlighted institutional barriers and their own limited proficiency in experiential learning (EL) techniques. Practical Implications : The study proposed institution-wide, systemic strategies to improve faculty and student engagement in EL. The study also provided policy recommendations, which included establishing accountability frameworks, defining credit benchmarks, and incorporating faculty incentivization mechanisms. Originality : Unlike prior research that examined faculty and student challenges in isolation, this study explored their interconnections. It extended Kolb’s Experiential Learning Model by demonstrating how perceptual gaps, institutional limitations, and faculty constraints disrupted learner-educator interaction, particularly at the early stages of the EL cycle.